A Randomized Pilot Clinical Trial of Pravastatin Versus Placebo in Pregnant Patients at High Risk of Preeclampsia. Issue 3 (24th September 2022) - Constantine, M.M.; West, H.; Wisner, K.L.; Caritis, S.; Clark, S.; Venkataramanan, R.; Stika, C.S.; Rytting, E.; Wang, X.; Ahmed, M.S.
Abstract : ( Am J Obstet Gynecol . 2021;225:666.e1–15) Preeclampsia affects up to 8% of pregnancies and is associated with maternal and neonatal morbidities. Preeclampsia also shares characteristics with other cardiovascular diseases. Pravastatin has been considered a possible method of preventing preeclampsia, supported by preclinical studies and pilot clinical studies using 10 mg pravastatin in high-risk patients. This study aimed to determine the safety and pharmacokinetic parameters of 20 mg pravastatin in patients with a high risk of preeclampsia.